ArxA From Azoarcus sp. CIB, an Anaerobic Arsenite Oxidase From an Obligate Heterotrophic and Mesophilic Bacterium - Durante-Rodríguez, Gonzalo; Fernández-Llamosas, Helga; Alonso-Fernandes, Elena; Fernández-Muñiz, María Nieves; Muñoz-Olivas, Riansares; Díaz, Eduardo; Carmona, Manuel (Frontiers in Microbiology, 2019)
Arsenic is a toxic element widely distributed in nature, but numerous bacteria are able to resist its toxicity mainly through the ars genes encoding an arsenate reductase and an arsenite efflux pump. Some “arsenotrophic” bacteria are also able to use arsenite as energy supplier during autotrophic growth by coupling anaerobic arsenite oxidation via the arx gene products to nitrate respiration or photosynthesis. Here we have demonstrated that Azoarcus sp. CIB, a facultative anaerobic β-Proteobacterium, is able to resist arsenic oxyanions both under aerobic and anaerobic conditions. Genome mining, gene expression and mutagenesis studies revealed the presence of a genomic island that harbors the ars and arx clusters involved in arsenic resistance in strain CIB. Orthologous ars clusters are widely distributed in the genomes of sequenced Azoarcus strains. Interestingly, genetic and metabolic approaches showed that the arx cluster of the CIB strain encodes an anaerobic arsenite oxidase also involved in the use of arsenite as energy source. Hence, Azoarcus sp. CIB represents the prototype of an obligate heterotrophic bacterium able to use arsenite as an extra-energy source for anaerobic cell growth. The arsenic island of strain CIB supports the notion that metabolic and energetic skills can be gained by genetic mobile elements.